Current status of pig liver xenotransplantation. (November 2015) - Ekser, Burcin; Markmann, James F.; Tector, A. Joseph
Abstract: The shortage of organs from deceased human donors is a major problem limiting the number of organs transplanted each year and results in the death of thousands of patients on the waiting list. Pigs are currently the preferred species for clinical organ xenotransplantation. Progress in genetically-engineered (GE) pig liver xenotransplantation increased graft and recipient survival from hours with unmodified pig livers to up to 9 days with normal to near-normal liver function. Deletion of genes such as GGTA1 (Gal-knockout pigs) or adding genes such as human complement regulatory proteins (hCD55, hCD46 expressing pigs) enabled hyperacute rejection to be overcome. Although survival up to 9 days was recorded, extended pig graft survival was not achieved due to lethal thrombocytopenia. The current status of GE pig liver xenotransplantation with world experience, potential factors causing thrombocytopenia, new targets on pig endothelial cells, and novel GE pigs with more genes deletion to avoid remaining antibody response, such as beta1, 4-N-acetyl galactosaminyl transferase 2 (β4GalNT2), are discussed. Highlights: Progress in genetically-engineered pig liver xenotransplantation increased graft and recipient survival up to 9 days. Extended survival more than 9 days was not achieved due to lethal thrombocytopenia and coagulopathy. The current review discusses the world experience in preclinical genetically-engineered pig liver xenotransplantation. New preclinical studies in pig-to-primate liver xenotransplantation are warranted using newly available genetically-engineered pigs.